Infralimbic cortex is required for learning alternatives to prelimbic promoted associations through reciprocal connectivity - Arghya Mukherjee (Nature Portfolio, 2018)
Prelimbic (PL) and infralimbic (IL) cortical areas are known to have complementary roles in learning and decision making. Here the authors report reciprocal connectivity between the two areas and elucidate their functional impact on different aspects of learning.